1998
DOI: 10.1111/j.1349-7006.1998.tb00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44 Variants and Its Association with Survival in Pancreatic Cancer

Abstract: Since the CD44 variant 6(v6) molecule has been noted as a marker for tumor metastasis and prognosis in several tumors, we examined whether or not v6 is a useful marker for evaluating the prognosis of pancreatic cancer patients. In addition, we attempted to assess the clinicopathological implications for pancreatic cancer of the variant 2 (v2) isoform using a recently developed monoclonal antibody against a v2 epitope. The expression of CD44 variants was evaluated immunohistochemically in paraffin-embedded panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…Several studies have associated CD44 expression with tumor progression and metastasis, whereas others maintain that CD44-positive cells exhibit a favorable prognosis. Studies have found increased levels of CD44 variant isoform expression correlating with poor prognosis in diseases, such as thyroid cancer, prostate cancer, renal cell carcinoma, and breast cancer; whereas others have shown decreased levels of CD44 correlating with good prognosis in head and neck carcinomas, prostate, colon cancer, breast cancer, and neuroblastoma (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In vitro data showing that the effects of CD44 engagement with hyaluronan during cancer progression and metastatic spread seem cell type specific and dependent upon CD44 isoform expression.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have associated CD44 expression with tumor progression and metastasis, whereas others maintain that CD44-positive cells exhibit a favorable prognosis. Studies have found increased levels of CD44 variant isoform expression correlating with poor prognosis in diseases, such as thyroid cancer, prostate cancer, renal cell carcinoma, and breast cancer; whereas others have shown decreased levels of CD44 correlating with good prognosis in head and neck carcinomas, prostate, colon cancer, breast cancer, and neuroblastoma (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In vitro data showing that the effects of CD44 engagement with hyaluronan during cancer progression and metastatic spread seem cell type specific and dependent upon CD44 isoform expression.…”
Section: Introductionmentioning
confidence: 99%
“…The cell adhesion molecule CD44 is a transmembrane glycoprotein overexpressed and linked to bad prognosis in a number of tumor entities such as breast (1)(2)(3) and pancreatic cancer (4,5), hepatocellular carcinoma (6) and hematologic malignancies (7). CD44 receptor varies in size and function owing to N-and O-glycosylation and alternative splicing, which affects predominantly the extracellular domain of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, using a recently developed monoclonal antibody against a CD44v2 epitope, we have demonstrated that CD44v2 expression was correlated significantly with poorer prognosis in breast cancer 15) and in pancreatic cancer. 16) Other reports show that the expression of CD44st is associated with longer survival in neuroblastoma 17) and that down-regulation of CD44v6 is associated with shorter survival in laryngeal squamous cell carcinoma. 18) We have proved that down-regulation of CD44v2 was correlated significantly with poorer prognosis in esophageal squamous cell carcinoma.…”
mentioning
confidence: 99%